1991
DOI: 10.1128/jb.173.12.3795-3802.1991
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a 1,2-dihydroxynaphthalene dioxygenase from a bacterium that degrades naphthalenesulfonic acids

Abstract: 1,2-Dihydroxynaphthalene dioxygenase was purified to homogeneity from a bacterium that degrades naphthalenesulfonic acids (strain BN6). The enzyme requires Fe2" for maximal activity and consists of eight identical subunits with a molecular weight of about 33,000. Analysis of the NH2-terminal amino acid sequence revealed a high degree of homology (22 of 29 amino acids) with the NH2-terminal amino acid sequence of 2,3-dihydroxybiphenyl dioxygenase from strain Pseudomonas paucimobiis Ql. 1,2-Dihydroxynaphthalene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 43 publications
5
97
1
Order By: Relevance
“…Other researchers (3,7,34,52) M-1 cm1-, 2% is 1,450 M-1 cm-1, 6323 is 2,520 M1 cm-', and e is 1,890 M-1 cm-1. was dissolved in D20 and then NaOH was added.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers (3,7,34,52) M-1 cm1-, 2% is 1,450 M-1 cm-1, 6323 is 2,520 M1 cm-', and e is 1,890 M-1 cm-1. was dissolved in D20 and then NaOH was added.…”
Section: Resultsmentioning
confidence: 99%
“…Misidentification of tHBPA as the cis isomer in previous work (3,7,34,52) has been a factor which has complicated a complete understanding of the naphthalene pathway. Barnsley (3) identified the first product of ring cleavage of 1,2-dihydroxynaphthalene as HCCA and showed that this compound isomerized spontaneously to form an equilibrium mixture with a compound that he identified as cHBPA.…”
Section: Discussionmentioning
confidence: 99%
“…In silico identification of the genes encoding the NsaC, NsaD, NsaE and NsaF involved in the degradation of naphthalenesulfonates NsaC and NsaE from S. xenophaga BN6 have previously been purified and their N-terminal amino acid sequences determined (Kuhm et al, 1991a(Kuhm et al, , 1992. This allowed the identification of ORF7 and ORF13 as the genes encoding the NsaC and NsaE of the naphthalenesulfonate pathway, because the N-terminal 29 or 26 aa of the predicted protein sequences were identical to the data obtained experimentally by protein sequencing.…”
Section: Biochemical Analysis Of the Deletion Mutants In The Genes Prmentioning
confidence: 99%
“…Three of the relevant enzymes, NsaC, NsaD and NsaE, have been purified and biochemically characterized. Furthermore, the N-terminal amino acid sequences of NsaC and NsaE have been determined (Kuhm et al, 1991a(Kuhm et al, , 1992(Kuhm et al, , 1993.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation